Motivations of postgraduate dental students in Australia and New Zealand to pursue a dental specialty training program and their concerns - Li Ho, Amy Vei (Heliyon, 2021)
OBJECTIVES: To determine the motivations of postgraduate dental students to pursue a specialist dental career and their concerns prior to and during the program. METHODS: A 3-part online survey comprising of participants’ background, motivations and concerns and quality of life during the program, was distributed to students enrolled in the Doctor of Clinical Dentistry program in Australia and New Zealand from April to May 2018. Participation was voluntary and anonymous. Two separate reminders were provided two and four weeks after the initial survey was distributed. RESULTS: There was a 53.6% response rate (97/181 participants). The main factor for pursing a dental specialist degree was intellectual stimulation. Participants who were aged 40 years and above and those who were divorced/separated were most concerned about the amount of study required and finances during the program. Participants in their final year were most concerned about their personal relationships during the program. Orthodontic, oral medicine and paedodontic trainees reported concerns about the lack of exposure of their specialty during undergraduate training while periodontics and orthodontic trainees reported having the least exposure while working. CONCLUSION: This study showed that dental specialist trainees in Australia and New Zealand were primarily motivated to pursue a specialty for intellectual stimulation. Most students were concerned about the amount of study required, finances and having a work/life balance during the training program. Most students planned to work as associates in private practice upon graduation. Financial benefits may be required to stimulate an interest in academia. CLINICAL SIGNIFICANCE: An understanding of the motivations of postgraduate students is important to help dental programs mentor students in their future career pathway, improve the selection of candidates for the specialty programs and identify key areas to provide support, prior to, or during the program.